FACTORS INFLUENCING TOURIST SATISFACTION WITH AGRITOURISM IN THE MEKONG DELTA, VIETNAM - Nguyen Truong SON; Quoc Nghi NGUYEN; Thi Hong Loc HOANG (Geo Journal of Tourism and Geosites, 2023)
The Mekong Delta, Vietnam possesses great potential and advantages for developing agritourism. To ensure the sustainable development of agritourism, enhance service quality, and improve tourist satisfaction are essential. This study aims to identify the factors influencing tourist satisfaction with agritourism in the Mekong Delta. Data were collected using a quota sampling method, with a sample size of 228 tourists who had visited and experienced agritourism in the Mekong Delta, Vietnam. A mixed-method approach combining qualitative and quantitative research was used to test research hypotheses. By applying structural equation modeling (SEM), the study demonstrated that local culture, natural landscape, novelty, assurance, tourism human resources, and perceived value positively influenced tourist satisfaction with agritourism in the Mekong Delta. Among these factors, the natural landscape had the most impact on tourist satisfaction with agritourism in the Mekong Delta